METODE PENAPISAN CABAI (CAPSICUM ANNUUM L.) UNTUK KETAHANAN TERHADAP CHILLI VEINAL MOTTLE VIRUS (Chi VMV) DAN CUCUMBER MOSAIC VIRUS (CMV) - Latifah, Sri Hendrastuti Hidayat, dan Sriani Sujiprihati . (Universitas Lampung, 2008)
Screening Method for Chilli Veinal Mottle Virus (Chi VMV) and Cucumber Mosaic Virus (CMV) Resistance in Chillipepper. ChiVMV and CMV have been reported as the causal agents of main diseases in chillipepper in Indonesia and other Asian countries. Mix infection of this two viruses was commonly occurred in the field, causing severe disease . The use of resistance varieties has been proposed for dealing with the yield losses causing by the viruses. Breeding program is undergoing for development of chillipepper varieties resistant to ChiVMV and CMV. Methodology for routine screening activity of chillipepper for resistance to both ChiVMV and CMV needs to be established. This research was conducted in Cikabayan Glass House and Plant Virology Laboratory, Plant Protection Department, Bogor Agricultural University from May 2006 to June 2007. Aim of the research was to develop screening method for simultaneous infection by the two viruses, ChiVMV and CMV. Inoculation of ChiVMV and CMV was done by single inoculation or repetitive inoculation methods. In both methods, ChiVMV and CMV were inoculated in different sequences, either ChiVMV or CMV first. The result showed that incubation period was shorter when CMV was inoculated in advance both in single and repetitive inoculation method. Mosaic, mottle and malformation type symptom was observed in infected plants. Based on disease incidence, infection of ChiVMV was higher compared to CMV in repetitive inoculation as well as in single inoculation. Repetitive inoculation methods with virus sequence ChiVMV-CMV-ChiVMV-CMV was selected for resistance evaluation of chillipepper genotypes.